The Work Environment of Welding Operators at Volvo Group Trucks Operations : An Investigation to Reduce the Risk of Musculoskeletal Disorders Among Welders - Jonsson Roos, Linda (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
This master thesis report presents a 20 weeks long project within Industrial design engineering at Luleå University of Technology, performed at Volvo Group Trucks Operations in Umeå. Since the company from a previous study knew that the operators on segment two work in unfavorable work postures, a further investigation of the operators’ work environment was needed. Therefore, the subject of investigation in this project became the physical workload and more specifically, the factors related to the appearance of work related musculoskeletal disorders (MSDs). Segment two is positioned at the end of Volvos’ production line called finishline where the work is primarily done manual by two shift teams with approximately 14 operators in each one. The project objective was to map the current situation for the manual welding operators at segment two and identify potential ergonomic risks within their everyday work. The focus was placed on finding improvements that could decrease the operators’ risk for developing MSDs during work. The project aim was to develop improvements that direct, and over a longer time span, could ease and improve the operators work situation. By observing, filming, interviewing and hand out questionnaires, the current state for the operators could be mapped. Three interviews were held, 22 questionnaires were answered and almost 50 film sequences were made. The work on segment two are station based where the operators are allocated a specific time for each operation within the station. Usually, the operators rotate after ten truck cabs and then move to the next station. The work consists of screwing, welding, grinding, drilling and controlling. The situation analysis was done by investigating the questionnaire responses further, explore the body postural MSD risks with help of RULA and REBA and using the software AviX to let the operators self-estimate the strain in different muscle groups during work. According to the questionnaires, the operators are highly or partly strained physical and ...